A Sn-stabilized Cuδ+ electrocatalyst toward highly selective CO2-to-CO in a wide potential range. Issue 40 (6th October 2022) - Tan, Xingxing; Guo, Weiwei; Liu, Shoujie; Jia, Shunhan; Xu, Liang; Feng, Jiaqi; Yan, Xupeng; Chen, Chunjun; Zhu, Qinggong; Sun, Xiaofu; Han, Buxing
Abstract : Sn-stabilized Cu δ + electrocatalysts have been prepared, achieving highly selective CO2 -to-CO in a wide potential range. The modifier Sn could tune the electronic structure of Cu, resulting in high reactivity and selectivity for CO production. Abstract : Current techno-economic evaluation manifests that the electrochemical CO2 reduction reaction (eCO2 RR) to CO is very promising considering its simple two-electron transfer process, minimum cost of electricity, and low separation cost. Herein, we report a Sn-modification strategy that can tune the local electronic structure of Cu with an appropriate valence. The as-prepared catalysts can alter the broad product distribution of Cu-based eCO2 RR to predominantly generate CO. CO faradaic efficiency (FE) remained above 96% in the wide potential range of −0.5 to −0.9 V vs. the reversible hydrogen electrode (RHE) with CO partial current density up to 265 mA cm −2 . The catalyst also had remarkable stability. Operando experiments and density functional theory calculations demonstrated that the surface Cu δ + sites could be modulated and stabilized after introducing Sn. The Cu δ + sites with low positive valence were conducive to regulating the binding energy of intermediates and resulted in high CO selectivity and maintained the stability of the catalyst. Additionally, scaling up the catalyst into a membrane electrode assemble system (MEA) could achieve a high overall current of 1.3 A with exclusive and stable CO generation.